16 Decisions and discussions relating to dnacpr in a regional cancer centre. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Griffiths, Ann; Monnery, Daniel; Coackley, Alison; Watson, Amanda; Benson, Sinead; Cadwallader, Claire; Cooper, Malcom
Abstract : Background: In 2014 the family of a woman who died in one of Britain's best-known hospitals won their legal claim that her rights were violated when a Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) document was completed without her or her family being consulted. A judicial review noted that Article 8 of the Human Rights Act was breached, concluding that there is a duty to consult patients and/or those important to them in relation to DNACPR unless that consultation may result in physical or psychological harm; this is more than just causing distress. Aim: Audit practice regarding DNACPR decisions and the discussions surrounding them in a tertiary cancer centre. Methods: A retrospective case note review of patients' in whom a DNACPR had been placed was conducted in December 2016. Practice was compared against the 2016 Joint Statement, 'Decisions relating to cardiopulmonary resuscitation'. Results: 22 case notes were reviewed in which a DNACPR was completed; 19 due to futility in cases of terminal cancer and 3 due to patient choice. In 3 cases no consultation had taken place. The reasons for this included patient/family declining a discussion and risk of harm. In 4/22 cases there was no documentation of the clinical reasoning for a DNACPR decision. In 1 case the consultation led to potentially avoidable patient distress. In 7 cases the patient lacked mental capacity to participate in a consultation; in 1 case it was felt it would cause too much harm to discuss the decision with their family. Conclusion: Patients and those important to them should be made aware of DNACPR decisions and these conversations recorded, including reasons for the decision. This audit however has highlighted ongoing variability in practice. Further training is needed in order to standardise practice and ensure high quality consultations around this sensitive topic are undertaken.